PENGEMBANGAN KURIKULUM DAYAH COT KALA PADA ERA KERAJAAN PERLAK, ACEH - Mannan Mannan (MIQOT, 2022)
Abstract: This study examines the development of the Dayah Cot Kala curriculum during the Perlak Kingdom. The curriculum of Islamic educational institutions has changed from time to time. This is influenced by various factors, ranging from the demands of the times, state policies, and the socio-culture of the surrounding community. Using a historical approach, this literature study proposes the findings that Dayah Cot Kala in the era of the Perlak Kingdom was the first Islamic educational institution in Indonesia and even in Southeast Asia. This dayah already has an ideal curriculum that is ahead of its time, and does not recognize the dichotomy between religious education and general education as happened to the dayah institution during its decline, both during the colonial period and the post-colonial period. This study aims to determine the factors that influence curriculum development at that time.Keywords: curriculum, Islamic education, dayah, Aceh, the Kingdom of PerlakAbstrak: Studi ini mengkaji pengembangan kurikulum Dayah Cot Kala pada masa Kerajaan Perlak. Kurikulum lembaga pendidikan Islam mengalami perubahan dari masa ke masa. Hal ini dipengaruhi oleh berbagai faktor, mulai dari tuntutan zaman, kebijakan negara, dan sosial budaya masyarakat di sekitarnya. Dengan menggunakan pendekatan historis, studi kepustakaan ini mengajukan temuan bahwa Dayah Cot Kala di era Kerajaan Perlak merupakan lembaga pendidikan Islam pertama kali di Indonesia bahkan di Asia Tenggara. Dayah ini telah mempunyai kurikulum yang ideal dan mendahului masanya, juga tidak mengenal dikotomi antara pendidikan agama dengan pendidikan umum sebagaimana yang terjadi pada lembaga dayah di masa kemundurannya, baik pada masa penjajahan dan masa pasca penjajahan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi pengembangan kurikulum pada masa itu.Kata Kunci: kurikulum, pendidikan Islam, dayah, Aceh, Kerajaan Perlak